Flexible Crossbar‐Structured Phase Change Memory Array via Mo‐Based Interfacial Physical Lift‐Off. (20th December 2018) - Kim, Do Hyun; Lee, Han Eol; You, Byoung Kuk; Cho, Sung Beom; Mishra, Rohan; Kang, Il‐Suk; Lee, Keon Jae
Abstract: Inorganic phase change memories (PCMs) have attracted substantial attention as a next‐generation storage node, due to their high‐level of performance, reliability, and scalability. To integrate the PCM on plastic substrates, the reset power should be minimized to avoid thermal degradation of polymers and adjacent cells. Additionally, flexible phase change random access memory remains unsolved due to the absence of the optimal transfer method and the selection device. Here, an Mo‐based interfacial physical lift‐off transfer method is introduced to realize a crossbar‐structured flexible PCM array, which employs a Schottky diode (SD) selection device and conductive filament PCM storage node. A 32 × 32 parallel array of 1 SD‐1 CFPCM, which utilizes a Ni filament as a nanoheater for low power phase transition, is physically exfoliated from the glass substrate at the face‐centered cubic/body‐centered cubic interface within the sacrificial Mo layer. First principles density functional theory calculations are utilized to understand the mechanism of the Mo‐based exfoliation phenomena and the observed metastable Mo phase. The flexible 1 SD‐1 CFPCM shows reliable operations (e.g., large resistance ratio of 17, excellent endurance over 100 cycles, and long retention over 10 4 s) with excellent flexibility. Furthermore, the random access operation is confirmed by addressing tests of characters "KAIST." Abstract : A flexible crossbar‐structured phase change memory (PCM) array is realized via an Mo‐based interfacial physical lift‐off transfer method. Strain‐induced phase transformation of the upper sacrificial Mo layer enables the parallel memory array employing one Schottky diode‐one conductive filament PCM to be exfoliated from the glass substrate at the face‐centered cubic/body‐centered cubic Mo interface. The flexible memory presents reliable operations with excellent flexibility.